VERIFICATION DE DIMENSIONNEMENT D’UNE COLONNE DE RECTIFICATION : (Dé-butaniseur de Hassi R’MEL) - BOUCHOUIREB YOUCEF; TALEB ABDELRRAZAK; MERIGUI Khaled (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : GÉNIE DES PROCÉDÉS, 2023)
Our memoir consists of studying a distillation column (debutanizer), this study is divided into two parts: In a first part, a dimensioning of this column by precise method by simulation with the HYSYS software. When we compare these results with those we have obtained and those observed through the values obtained by this program and the values at treatment room level, the results are close to a large percentage. In a second part, a mechanical study to verify the resistance of the studied column according to the manufacturer's data and a hydrodynamic study for the verification of the trays correct functioning.
OPTION : Génie pétrochimique